Dynamics of Islamic Economics Education and Learning In The Digital Age: A Global Study Educational Transformation - Marlina, Reni; Saefullah, Selvia Ru’yatus; Prasetyo, Yoyok; Sakuroh, Lilis; Adiningsih, Neni Utami (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Global technological transformation has influenced various aspects of education, including the management of Islamic economics learning. These changes require managerial strategies that are not only adaptive to digital developments but also remain consistent with Islamic principles. This article aims to critically review and analyze the practice of Islamic economics learning management in various countries in the context of technological innovation. The method used is a qualitative literature study, based on an examination of eighteen relevant scientific documents, including journals, research reports, and education policy documents. The results of the study show disparities in managerial practices between institutions in Muslim-majority and Muslim-minority countries, both in terms of the integration of Islamic values, digital readiness, and academic leadership. Institutions that develop value-based learning systems supported by transformational leadership tend to be more successful in responding to changing times. A curriculum integrated with the halal industry context and the use of technology that internalizes the principles of maqashid sharia are characteristics of an innovative and valuable learning model. This study concludes that the development of sharia economics learning management needs to be directed towards a model that is not only responsive to technological disruption but also strongly rooted in Islamic ethics and global needs.